Effect of microRNA-29b on proliferation, migration, and invasion of endometrial cancer cells. Issue 8 (August 2019) - Kong, Jian; He, Xiuting; Wang, Yan; Li, Jie
Objective: Aberrant expression of microRNAs is a key regulator of tumorigenesis and progression in endometrial cancer. We assessed the effect of microRNA-29b (miR-29b) on proliferation, chemosensitivity, migration, and invasion of endometrial cancer cells. Methods: The proliferation of endometrial cancer cells was examined by water-soluble tetrazolium (WST)-1 assay. The effects of miR-29b on migration and invasion were evaluated by transwell migration and Matrigel invasion assays. Western blotting was used to assess protein expression levels after altered expression of miR-29b. The effect of miR-29b on cisplatin-induced apoptosis was examined by Caspase-Glo 3/7 assay. Results: miR-29b inhibited proliferation and decreased migration and invasion of endometrial cancer cells. It also enhanced the sensitivity of endometrial cancer cells to cisplatin and increased cisplatin-induced apoptosis by regulating expression of BAX and Bcl-2. Moreover, miR-29b changed the expression level of phosphatase and tensin homolog (PTEN) and p-AKT by directly binding to the 3′ untranslated region of PTEN. Conclusion: miR-29b played important roles in proliferation and progression in endometrial cancer cells by direct regulation of PTEN. It might be used as a biomarker to predict chemotherapy response and prognosis in endometrial cancer.